1992
DOI: 10.1111/j.1365-2222.1992.tb03099.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemopoietic growth factors induce human basophil migration in vitro

Abstract: Accumulation of basophils in inflammatory sites is an important aspect of the late-phase allergic reaction involving skin and upper and lower airways, suggesting the existence of mechanisms for basophil migration. Because haemopoietic growth factors have been shown to stimulate various functions of human basophils, we tested the ability of haemopoietic growth factors to migrate basophils in vitro. Both IL-3 and granulocyte-macrophage colony-stimulating factor (GM-CSF) induced migration of purified normal basop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Furthermore, our earlier study using Boyden chamber systems demonstrated that IL-3 potently enhances in vitro locomotive responses by basophils (11). The migratory response induced by IL-3 was chemokinetic rather than chemotactic.…”
Section: Basophil Tem By Il-3mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, our earlier study using Boyden chamber systems demonstrated that IL-3 potently enhances in vitro locomotive responses by basophils (11). The migratory response induced by IL-3 was chemokinetic rather than chemotactic.…”
Section: Basophil Tem By Il-3mentioning
confidence: 99%
“…We and others have demonstrated that IL-3 represents the most potent basophil-activating cytokine and stimulates various aspects of basophil functions, including mediator release (21,22), survival (23,24), motility (11), adhesiveness to the endothelium (14), and expression of activation markers (14). Our present finding that IL-3 potentiated basophil TEM broadens the current concept of the capacity of IL-3 to modulate allergic inflammatory responses by up-regulating basophil functions.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that normal human basophils possess functional receptors for IL-3, 26,27 and IL-3 exhibits diverse effects on human basophils, including development, 28 differentiation, 29 migration, 30 histamine release 31 and augmentation of cytokine generation, 5 but there is a paucity of data regarding its effect on basophil apoptosis. In 1992, Yamaguchi and colleagues demonstrated that IL-3 and granulocyte-macrophage colony-stimulating factor (GM-CSF) maintained the numbers of viable basophils in vitro, as determined by Trypan blue exclusion.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some of these cytokines directly induce mediator-secretion from basophils in allergic individuals (15)(16). Furthermore, such cytokines can promote differentiation, adhesion and migration in basophils (17)(18)(19)(20).…”
mentioning
confidence: 99%